Pengaruh Motivasi Belajar Terhadap Tingkat Keberhasilan Belajar Siswa pada Pembelajaran PJOK di SMP N 4 Kajen (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine whether learning motivation has an effect on student learning success and to find out how much influence learning motivation has on student learning success at SMP N 4 Kajen Pekalongan Regency. This type of research uses quantitative descriptive. The sample is 52 students from the total population of class VIII students of SMP N 4 Kajen. The sampling technique used is Simple Random Sampling or random selection of respondents. The data collection instruments used in this study were Questionnaires and Documentation. The results of the study based on the data obtained showed that learning motivation had a significant influence from the results of calculations using the F test (simultaneous test) showing that the f value of 7.165 was greater than the f table. , and the sig value of 0.010 is smaller than 0.050. And to find out how big the influence of learning motivation on student learning outcomes can be shown from the results of calculating the coefficient of determination using the Summary Model showing that R Square is 0.125, which means that the magnitude of the influence of learning motivation is 12.5%, and 87.5% is influenced by another factor.